Terrorism Emergency Response A Workbook for Responders - Sachs, Gordon M. (Prentice Hall, 2003)
Appropriate for all emergency response personnel -- EMS, fire, rescue, or law enforcement -- Terrorism Emergency Response is an ideal resource for critical thinking and response preparation. It begins by providing basic information regarding terrorist incidents and the agents commonly faced during these incidents. It follows with 70 case-based scenarios that any responder can use to help sharpen their decision making skills.